Efficiency of Using Drones and Boats in Monitoring the Security of the Pang Pang Bay Water Aerodrome Area - Maulana, Rangga; Wibowo, Untung; Wiyono, Demmy Setyo; Ardian, Dede (Sinergi International Journal of Logistics, 2023)
This research investigates the use of drones and boats in monitoring the security of the water aerodrome area in Pang-Pang Bay. The aim is to measure the efficiency of using these two tools, compare their performance results, and evaluate the implications of the research results for security and operational development in the region. This research integrates qualitative and quantitative approaches to understand the role and challenges of each tool.The research results show that the use of drones provides significant efficiency in quickly reaching the incident point, covering a wide area, and aerial views that are useful in routine monitoring. On the other hand, boats have the advantage of quick response in emergency situations, stability in bad weather, and the ability to provide immediate assistance to individuals on the water. The results of the comparative analysis between the use of drones and boats reflect the special advantages of each tool in various aspects.The implication of this research is that the development of a security surveillance strategy in Pang-Pang Bay must consider the wise use of both tools, depending on operational needs and weather conditions. In an ideal situation, the combined use of drones and boats can provide a comprehensive solution to maintaining water safety.This research also makes an important contribution to the technology's development and application in the context of security surveillance. In conclusion, this research provides an in-depth understanding of the use of drones and boats in monitoring the Pang-Pang Bay water aerodrome area and provides a strong foundation for the development of better and more effective surveillance strategies in the area.